Investigation of the solid state reactions by time-resolved X-ray diffraction while crystallizing kesterite Cu2ZnSnSe4 thin films - Yoo, Hye Sun; Wibowo, Rachmat Adhi; Hölzing, Astrid; Lechner, R.; Palm, J.; Jost, S.; Gowtham, M.; Sorin, F.; Louis, B.; Hock, Rainer (ELSEVIER SCIENCE SA, 2013)
The pentanary chalcogenide Cu2ZnSn(S,Se)(4) (CZTSSe) compound is attracting considerable attention as a low-cost and high-efficient solar cell. The band gap can be tuned by adding Se to pure kesterite Cu2ZnSnS4, which influences the crystallization kinetics. The investigation of the crystallization of the pure selenium (Se) compound Cu2ZnSnSe4 can be helpful in understanding the reaction path between the elements of CZTSSe. Sputtered Cu-poor intermetallic Cu-Zn-Sn precursors were deposited on Mo-coated polyimide foil and sequentially capped by a thermally evaporated Se layer. Two different amounts of Se were deposited: amount that exactly matches the composition of Cu2ZnSnSe4; and that corresponding to twofold excess of the compound's element ratio. These two compositions were chosen to investigate influences of the amount of Se on the reaction path and kinetics. Also, the reaction of pure metallic Sn with Se was studied by stacking Sn layers on Mo-coated foils for observing a Sn-loss phenomenon. It was also deposited with two different amounts of Se matching approximately the compositions of SnSe and SnSe2. Time-resolved X-ray diffraction was employed to measure the solid state reactions while increasing the sample temperature up to 550 degrees C at a rate of 0.5 K/s in an evacuated reaction chamber. After the experiment, sample is analyzed by Raman spectroscopy to distinguish the CZTSe from secondary phases. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cu2ZnSnSe(4); CZTSe; SnSe; Sputtering; Formation reaction; In-situ XRD; Raman